Factors Affecting Financial Sustainability Ratio of Sharia Rural Banks in Java Island, 2013-2018 - Fitroh Safaah; Rosida Dwi Ayuningtyas (Journal of Islamic Economics Lariba, 2019)
This study aims to determine the influence of factors that influence the financial sustainability ratio (FSR) of Sharia Rural Banks (BPRS) on the island of Java in 2013-2018. The variables used in this study are financial sustainability ratio (FSR), non-performing financing (NPF), return on assets (ROA), financing debt ratio (FDR), operational expenses and capital adequacy ratio (BOPO) and capital adequacy ratio (CAR). The samples selected in this study were 23 BPRS most complete out 91 BPRS on the island of Java with a range of research from 2013 to 2018, where the samples were published by the annual financial statements at Bank Indonesia (BI) or at the Financial Services Authority (OJK). Analysis of the data used is panel data regression with the Fixed Effect method using the eviews 9 program tool. In the test results that the CAR variable partially has a significant positive effect on the Financial Sustainability Ratio (FSR) while the BOPO variable partially has a significant negative effect on the Financial Sustainability Ratio (FSR). Based on the results of the BPRS Amanah Sejahtera has the highest FSR value of 6,647.5167, while the lowest FSR value is the Attaqwa SRB of 138,5008.